1974
DOI: 10.1042/bj1380387
|View full text |Cite
|
Sign up to set email alerts
|

3-Mercaptopicolinic acid, an inhibitor of gluconeogenesis

Abstract: 1. 3-Mercaptopicolinic acid (SK&F 34288) inhibited gluconeogenesis in vitro, with lactate as substrate, in rat kidney-cortex and liver slices. 2. In perfused rat livers, gluconeogenesis was inhibited when lactate, pyruvate or alanine served as substrate, but not with fructose, suggesting pyruvate carboxylase or phosphoenolpyruvate carboxylase as the site of inhibition. No significant effects were evident in O(2) consumption, hepatic glycogen, urea production, or [lactate]/[pyruvate] ratios. 3. A hypoglycaemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(76 citation statements)
references
References 15 publications
6
69
0
1
Order By: Relevance
“…As shown in Table 1, in periportal hepatocytes (in which glutamine synthetase activity was less than 10% of total hepatocyte glutamine synthetase activity) stimulation of glycogen synthesis by alanine, proline and asparagine was as observed in total hepatocyte preparations [I] (see also below) and was further enhanced by the presence of 3-mercaptopicolinic acid, an inhibitor of phosphoenolpyruvate carboxykinase [17], which is in agreement with similar observations in total hepatocyte preparations [I, 41.…”
Section: Resultssupporting
confidence: 77%
“…As shown in Table 1, in periportal hepatocytes (in which glutamine synthetase activity was less than 10% of total hepatocyte glutamine synthetase activity) stimulation of glycogen synthesis by alanine, proline and asparagine was as observed in total hepatocyte preparations [I] (see also below) and was further enhanced by the presence of 3-mercaptopicolinic acid, an inhibitor of phosphoenolpyruvate carboxykinase [17], which is in agreement with similar observations in total hepatocyte preparations [I, 41.…”
Section: Resultssupporting
confidence: 77%
“…The concentration of glycerol 1 -phosphate increased rapidly to reach a peak level within 6 min whereas that of fructose 2,6-bisphosphate decreased more slowly over a period of about 10 min. We also observed that the gluconeogenic inhibitor, 3-mercaptopicolinate [35], reduced the accumulation of glycerol 1-phosphate by about 50% but had no effect on fructose 2,6-bisphosphate levels.…”
Section: Fructose 26-bisphosphate Concentration and Glycolytic Fluxmentioning
confidence: 58%
“…For the insulin tolerance test, nonfasted mice were injected intraperitoneally with human regular insulin (0.75 U/kg). For the pyruvate challenge test, mice deprived of food for 16 hours were injected intraperitoneally with pyruvate dissolved in saline (2 g/kg); where indicated, 3-mercaptopicolinic acid (3-MPA; 30 mg/kg), an inhibitor of gluconeogenesis (21,22), was administered orally 30 minutes before the test. The 3-MPA was synthesized as described (23).…”
Section: Methodsmentioning
confidence: 99%